2011
DOI: 10.1002/aic.12586
|View full text |Cite
|
Sign up to set email alerts
|

Multistage rotor‐stator spinning disc reactor

Abstract: The scale up of a rotor-stator spinning disc reactor by stacking single stage rotorstator units in series is demonstrated. The gas-liquid mass transfer per stage is equal to the mass transfer in a single stage spinning disc reactor. The pressure drop per stage increases with increasing rotational disc speed and liquid flow rate. The pressure drop is more than a factor 2 higher for gas-liquid flow than for liquid flow only, and is up to 0.64 bar at 459 rad s À1 . The high mass and heat transfer coefficients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 20 publications
(27 reference statements)
1
57
0
Order By: Relevance
“…The mass transfer at the membrane surface is assumed very high because of the very high mixing of the electrolyte at the membrane surface which is elaborated in our earlier paper [12]. Thus, the boundary layer thickness is calculated from the measured mass transfer in a rotor-stator spinning disc reactor which is proved to have a very high mass transfer coefficient [35]. The concentration jump of ionic species at the solution and the membrane interface for both anolyte and catholyte sides are depicted in Fig.…”
Section: Model Approachmentioning
confidence: 99%
“…The mass transfer at the membrane surface is assumed very high because of the very high mixing of the electrolyte at the membrane surface which is elaborated in our earlier paper [12]. Thus, the boundary layer thickness is calculated from the measured mass transfer in a rotor-stator spinning disc reactor which is proved to have a very high mass transfer coefficient [35]. The concentration jump of ionic species at the solution and the membrane interface for both anolyte and catholyte sides are depicted in Fig.…”
Section: Model Approachmentioning
confidence: 99%
“…18 Multiple discs were mounted on a single rotational axis to obtain ideally stirred tanks-in-series, which ultimately will lead to more plug flow behavior of the fluid flow in the reactor. 7,19 Therefore, this reactor is a promising tool to achieve process intensification goals, for example, realize a reduction of equipment volume, enhance volumetric productivity, and increase of mass-transfer rates in continuous flow reactors. This article presents the residence time distribution in the rotor-stator spinning disc reactor as a function of the rotational disc speed, axial disc spacing, and the volumetric flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…In a novel rotor-stator spinning disc reactor, Meeuwse et al [118] reported that the mass transfer coeffi cient ( k GL a GL ) is one order of magnitude higher than the conventional reactor system; however, the energy input is around three orders of magnitude higher ( Figure 30 transfer per unit of energy dissipation is around 80 ml 3 MJ -1 [121] . From Figure 23 is can also be seen that the mass transfer coeffi cient is higher as compared to the conventional equipment [118][119][120]. The higher mass transfer coeffi cients in the rotor-stator spinning disc reactor can have a significant infl uence on the selectivity in the case of competitive or consecutive reactions.…”
Section: Spinning Disc Reactor Technologymentioning
confidence: 99%